Microscopic Simulation of Synchronized Flow in Oversaturated City Traffic: Effect of Driver's Speed Adaptation. Issue 1 (January 2015) - Hermanns, Gerhard; Hemmerle, Peter; Rehborn, Hubert; Koller, Micha; Kerner, Boris S.; Schreckenberg, Michael
Synchronized flow has been found recently in studies of empirical GPS probe-vehicle data collected in oversaturated city traffic. In this paper, results of simulations with a three-phase microscopic model from Kerner and Klenov are presented. These results show features of synchronized flow. The effect of the driver's speed adaptation was found to play the key role in understanding the emergence of synchronized flow in over-saturated city traffic. The physical meaning of the speed adaptation effect in oversaturated city traffic was explained, and the influence of the speed adaptation effect on the average speed and travel time in oversaturated city traffic was investigated.